Rule of Law and Environment Nexus in Saudi Arabia - Mahmood, Haider; Alanzi, Awad Ali (International Journal of Energy Economics and Policy, 2020)
The environmental quality of any country is heavily depending on the rule of law. The Saudi government targets and achieves many transformations to reduce the fossil energy and to shift to cleaner production. To achieve a cleaner environment, the law and order is very important factor. Therefore, we scrutinize the role of rule of law on the CO2 emissions of Saudi Arabia using the period 1996-2014. We found that the rule of law has a negative effect on the CO2 emissions of Saudi Arabia and energy consumption has a positive effect. However, we corroborated the insignificant effects of income. We refer the Saudi legal authorities to further improve the rule of law in the country as it has significant positive environmental contribution by reducing CO2 emissions. Keywords: CO2 emissions, Rule of Law, Income, Energy Consumption JEL Classifications: Q53, P48, E01, K32 DOI: https://doi.org/10.32479/ijeep.9349